Knowledge, Attitude and Practices Towards Dengue Fever Among Slum Dwellers: A Case Study in Dhaka City, Bangladesh - Md. Mostafizur Rahman; Kamrun Nahar Tanni; Tuly Roy; Md. Rakibul Islam; Md. Alim Al Raji Rumi; Mohammed Sadman Sakib; Masrur Abdul Quader; Nafee-; Ifta Alam Shobuj; Afra Sayara Rahman; Md. Iftekharul Haque; Fariha Faruk; et al. (Frontiers Media S.A., 2023)
Objectives: This study intends to evaluate Dhaka city slum dwellers' responses to Dengue fever (DF).Methods: 745 individuals participated in a KAP survey that was pre-tested. Face-to-face interviews were performed to obtain data. Python with RStudio was used for data management and analysis. The multiple regression models were applied when applicable.Results: 50% of respondents were aware of the deadly effects of DF, its common symptoms, and its infectious nature. However, many were unaware that DF could be asymptomatic, a previously infected person could have DF again, and the virus could be passed to a fetus. Individuals agreed that their families, communities, and authorities should monitor and maintain their environment to prevent Aedes mosquito breeding. However, overall 60% of the study group had inadequate preventative measures. Many participants lacked necessary practices such as taking additional measures (cleaning and covering the water storage) and monitoring potential breeding places. Education and types of media for DF information were shown to promote DF prevention practices.Conclusion: Slum dwellers lack awareness and preventative activities that put them at risk for DF. Authorities must improve dengue surveillance. The findings suggest efficient knowledge distribution, community stimulation, and ongoing monitoring of preventative efforts to reduce DF. A multidisciplinary approach is needed to alter dwellers' behavior since DF control can be done by raising the population's level of life. People and communities must perform competently to eliminate vector breeding sites.